An innovative school-based intervention to promote healthy lifestyles. (October 2017) - Piana, Natalia; Ranucci, Claudia; Buratta, Livia; Foglia, Elena; Fabi, Marta; Novelli, Francesca; Casucci, Simone; Reginato, Elisa; Pippi, Roberto; Aiello, Cristina; Leonardi, Alessia; Romani, Giannermete; et al.
Objective: To describe an innovative school-based intervention to promote healthy lifestyles. To evaluate its effects on children's food habits and to highlight the key components which contribute most to the beneficial effects obtained from children's, teachers' and parents' perspectives. Design: An educational tool to improve personal awareness, promote healthy food choices and increase children's levels of physical activity was developed and evaluated. The tool used a community-based approach and included family members, schools, university, families, sports societies, farms, mass media and municipalities. Setting: A total of 11 primary school classes in five schools in Spoleto, Umbria. Methods: The tool dealt with healthy food choices, lifestyle and physical activities and is structured in four phases (4 months). The Kidmed test (a validated index based on principles sustaining Mediterranean dietary patterns as well as those that undermine them) and open-ended questionnaires (to highlight the key components which contributed most to the beneficial effects) were used to assess the effectiveness of the intervention. Kidmed scores were evaluated both before and after intervention (T0–T1) and the written answers collected (from teachers, parents and children) were subjected to content analysis using a form of grounded theory. Results: Data point to a significant before/after increase on Kidmed scores ( t  = −3.88; p  = .000), revealing an increase in children's adherence to the Mediterranean Diet, healthy habit changes, greater parental awareness of their educational responsibilities regarding food choices as well as physical activity, and a new school-family alliance as a result of the educational intervention. Conclusion: Project findings reveal positive effects on children's food habits and highlight key components necessary to enhance the effectiveness of a school-based educational intervention.